Heart rate dynamics in refractory and well controlled temporal lobe epilepsy - Ansakorpi, H; Korpelainen, J T; Huikuri, H V; Tolonen, U; Myllylä, V V; Isojärvi, J I T (Journal of neurology, neurosurgery and psychiatry, 2002)
Objectives: Disorders of cardiovascular and other autonomic nervous system functions are often found in patients with temporal lobe epilepsy (TLE). Cardiovascular dysregulation in TLE has previously been quantified assessing traditional time and frequency domain measures of heart rate (HR) variability from short term ECG recordings. However, new complexity and fractal measures of HR variability based on non-linear dynamics and fractals (“chaos theory”) may disclose certain patterns of HR dynamics that cannot be detected using only conventional measures. Methods: In addition to the traditional spectral and non-spectral components of HR variability, fractal correlation properties, approximate entropy (ApEn) of RR interval dynamics, and the slope of the power law relation were measured from 24 hour ambulatory ECG recordings to evaluate interictal autonomic cardiovascular regulatory function in 19 patients with refractory TLE, 25 patients with well controlled TLE, and in 34 healthy age and sex matched control subjects. Results: The traditional time and frequency domain measures were lower in patients with TLE than in controls (p<0.05). In addition, the power law slope (p<0.005) and ApEn (p<0.05) were also reduced in TLE patients. Furthermore, ApEn was smaller in patients with refractory TLE than in patients with well-controlled TLE ( p<0.01), whereas the long term fractal correlation value α2 was lower in patients with well controlled TLE (p<0.05). An altered HR variation was not associated with any particular AED regimen. Conclusions: In addition to reduced overall HR variability, the long term fractal organisation and complexity of HR dynamics seem to be altered in TLE. These abnormalities in HR behaviour may partly contribute to the occurrence of adverse cardiovascular events, such as life threatening arrhythmias in patients with TLE.